Evaluation of the Effect of Retightening and Mechanical Cycling on Preload Maintenance of Retention Screws - Delben, Juliana Aparecida [UNESP]; Gomes, Erica Alves [UNESP]; Ricardo Barao, Valentim Adelino [UNESP]; Assunção, Wirley Goncalves [UNESP] (Quintessence Publishing Co Inc, 2011)
Purpose: The aim of this study was to evaluate the effect of retightening and mechanical cycling on the maintenance of preload in the retention screws of implant-supported crowns. Materials and Methods: Five groups (n = 12 in each group) of implant-crown assemblies were created according to different abutments and veneering materials: Gold UCLA abutments cast in gold alloy veneered with ceramic (group 1) and light-curing resin (group 2), UCLA abutments cast in titanium veneered with ceramic (group 3) and light-curing resin (group 4), and zirconia abutments with ceramic veneering (group 5). The crowns were attached to implants by gold retention screws. The assemblies were submitted to mechanical cycling for a total of 1 million cycles. Removal torque measurements were performed initially and after each period of 100,000 cycles; this was followed by screw retightening with 35 Ncm of torque. Data were evaluated with analysis of variance, the paired t test, and the Student t test. Results: All groups exhibited reduced removal torque values in comparison to insertion torque initially and after all periods of mechanical cycling. Analysis of variance revealed statistically significant differences among the groups, but there were no differences among the periods of mechanical cycling or for the interaction between groups and cycling. Group I was the only group that did not show a difference between removal torque values of different cycling periods. The Student t test did not reveal statistically significant differences between mean removal torque values obtained before and after mechanical cycling, except for group 4. Conclusions: Torque maintenance allowed screw joint stability in the present study Mechanical cycling associated with the retightening of abutment screws did not influence the maintenance of insertion torque. INT J ORAL MAXILLOFAC IMPLANTS 2011;26:251-256
Keywords: implant; implant-supported prosthesis; torque; veneering material